Improvements in the Downstream Processing of rhGH production in Pichia pastoris: Optimization of hGH purification using activated carbon clarification in Pichia pastoris - Azadi, Saeed; Mortazavia, Seyed Alireza; Sadjady, Seyyed Kazem; Solaimanian, Roya; Naghdi, Nasser; Mahboubi, Arash (Iranian Journal of Pharmaceutical Sciences, 2018)
Production of human proteins in Pichia pastoris has significant advantages. However, there is still need for improvement of various stages of its downstream processing like clarification and purification. In fact downstream processes are usually the most critical part of production of biotech products. This work aimed to evaluate the effect of two steps added to the downstream processes of human growth hormone (hGH) production in Pichia pastoris. Firstly, the effect of clarification, with activated carbon, on capture of hGH by ion exchange chromatography (IEC) was investigated. For this purpose, a clarification process using activated carbon was used to remove process contaminants like pigments. The clarified sample was applied to the IEC column and the recovery of hGH, following IEC, was assessed using SDS-PAGE, Bradford protein assay, and area under the curve (AUC). The obtained results showed that the AUC values were 2.81 and 5.61 for the with- and without-treatment samples, respectively. Protein recovery of clarified sample with activated carbon was 541 mg in comparison with 328 mg for the sample without treatment. The yield of IEC was also improved from 50.46% to 83.23% following treatment with activated carbon. Secondly, the effect of three concentrations of ammonium sulfate in the binding buffer on resolution of hGH upon elution on hydrophobic interaction chromatography (HIC) was investigated. Biological activity was used as the main criterion for evaluation of purified hGH using HIC. The obtained results indicated that by increasing the concentration of ammonium sulfate form 1 to 3 mol/L, resolution of hGH was improved, as the purified fraction using 3 mol/L of ammonium sulfate showed a specific activity of 3.1IU/mg. So, the results of the present study demonstrated that activated carbon is a promising candidate for efficient clarification of recombinant hGH and for improving the efficiency of the capture step. Therefore, it can be considered by biotech companies as a cost-effective and sustainable clarification procedure of recombinant proteins from high cell density cultures. This study also revealed that 3% ammonium sulfate has a positive effect on the separation of hGH variants with the desired biological activity.